Duration of Hospital Stay and Treatment Pattern among Patients Undergoing Common Operative Procedures at tertiary care hospital in Nepal - Chaudhary, Sanjay; Chaurasia, Lokeshwar; Singh, Jitendra Kumar (Janaki Medical College Journal of Medical Science, 2019)
Background and Objectives: Appendectomy, cholecystectomy, fistulectomy, and herniotomy or herniorrhaphy are the most common surgical operations in Nepal. Despite the high prevalence and complexity of the patient population served by general and universal surgery services, little has been reported about the services, treatment procedures and outcomes. Therefore, the study is designed to investigate the duration of hospital stay, and treatment pattern among patients undergoing common surgical operative procedures at Janaki Medical College, Janakpur, Nepal. Material and methods: A prospective observational study was conducted among patients undergoing common surgical operative procedures at surgery department of Janaki Medical College (JMC) over a period of one year from January 2018 to December 2018. Patients of all age groups and gender undergoing surgical operative procedures; appendectomy, herniotomy cholecystectomy and fistulectomy were included in the study. The patients were assessed preoperatively, intra-operatively and postoperatively. Results: In a total of 325 patients, 11.1% of patients underwent fistulectomy, 14.5% underwent appendectomy, 35.4% underwent herniorrhaphy and 39.1% underwent cholecystectomy. Mean duration of stay at hospital for cholecystectomy was slightly higher (8.13±2.40 days) than other operating procedures: fistulectomy (5.44 ±1.48 days), appendectomy (7.40±2.00 days), and operative procedure of hernia (6.17±1.59 days). Most commonly used antibiotic for control of preoperative and post operative infection was third generation cephalosporin’s, ceftriaxone and cefixime. Conclusion: The study demonstrates longer duration of hospital stay for cholecystectomy as compared to other operating procedures like fistulectomy, appendectomy, herniorrhaphy, hernioplasty and herniotomy with significant difference by types of surgery. Most commonly used antibiotic for control of infection was third generation cephalosporin, ceftriaxone and cefixime.